Dormência física e atributos funcionais em sementes de leguminosas neotropicais - Pereira, Gustavo Ferreira (2022)
Dormancy is a state in which viable seeds fail to germinate, even under favorable conditions for germination. Physical dormancy (PY) occurs exclusively due to the impermeability of the seed coat or the pericarp, which have layers of juxtaposed cells containing hydrophobic substances that repel water. Due to the presence of this dormancy, artificial techniques are necessary to overcome it, and in the case of PY, the embryo can continue its development since it has no other impediment to germination. This dormancy class is recurrent in seeds of species of the Fabaceae family. The purpose of this work was to investigate the presence or absence of physical dormancy in seven species of the Fabaceae family, evaluate physical and physiological attributes of seeds, test effective artificial techniques to overcome dormancy and evaluate the storage tolerance. The following species were used in this work: Adenanthera pavonina, Copaifera langsdorffii, Dimorphandra mollis, Hymenaea courbaril, H. stigonocarpa, Ormosia arborea and Stryphnodendron adstringens. For C. langsdorffii seeds, an investigation into the relationship between aril and germination was also carried out. Imbibition tests with intact seeds and mechanically scarified, dormancy breaking tests using hot water treatments, mechanical and acid scarification with H2SO4 were carried out. Additionally, after 1 and 1,5 years of storage, the seeds were placed to germinate, evaluating whether they are tolerant to storage and the effect on dormancy. Seeds of six species showed PY, with only C. langsdorffii not having dormancy. Mechanical scarification was efficient in overcoming the dormancy of the six dormant species. For D. mollis, H. stigonocarpa and S. adstringens, immersion in water at high temperatures was efficient in breaking dormancy, while for O. arborea acid scarification effectively overcame seed dormancy. Seeds of D. mollis, H. courbaril, H. stigonocarpa, O. arborea, and S. adtringens are storage tolerant, while seeds of C. langsdorffii reduced germination during storage. The aril affects seed germination of C. langsdorffii but does not prevent water absorption. The behavior of species of the same family is different regarding the presence or absence of dormancy, response to dormancy breaking treatments and storage.